The impact of platelet functions and inflammatory status on the severity of preeclampsia - BİNGÖL ÖZAKPINAR, ÖZLEM; TETİK, ŞERMİN (TAYLOR & FRANCIS LTD, 2015)
Objective: To find out whether there is a correlation between the extent of platelet activation and inflammation and the severity of preeclampsia (PE) in the third trimester of pregnancy. Methods: Forty-one women with PE (n = 23 severe, n = 18 mild) and 80 normotensive pregnant (NP) women were included in the study. Their blood samples were obtained and interleukin (IL)-8 and IL-10 levels measured by an enzyme-linked immunosorbent assay. Basal CD61 and CD62P expressions on CD41-positive platelets were analyzed with the use of flow-cytometry. Platelet aggregation was induced by adenosine diphosphate and determined by aggregometry. Results: CD62P expression was increased in severely preeclamptic women, and the platelet aggregation was decreased in both mildly and severely preeclamptic women in comparison with NP women. However, CD61 expression was similar among the groups. An enhanced inflammatory response was seen in severely preeclamptic women demonstrated by increased levels of IL-8 and decreased levels of IL-10. However, the intensity of platelet activation did not correlate directly with the change in plasma levels of IL-8 and IL-10 in preeclamptic women. Conclusions: Platelets may have a role in the inflammatory response in PE. However, the severity of inflammation is found to be independent from the intensity of platelet activation in preeclamptic women. This seems to be related to mechanisms causing alterations of cytokine levels such as IL-8 and IL-10, rather than platelet activation.
Keywords: Aggregometry; inflammation; interleukins; platelet activation; preeclampsia; severity; NORMAL-PREGNANCY; PLASMA-LEVELS; AGGREGATION; ACTIVATION; EXPRESSION; CYTOKINES; IL-10; INTERLEUKIN-10; ADHESION; GMP-140